Use of 3D DCE-MRI for the estimation of renal perfusion and glomerular filtration rate: an intrasubject comparison of FLASH and KWIC with a comprehensive framework for evaluation - Eikefjord, Eli; Zöllner, Frank G. (American journal of roentgenology, 2015)
OBJECTIVE. The purpose of this article is to compare two 3D dynamic contrast-enhanced (DCE) MRI measurement techniques for MR renography, a radial k-space weighted image contrast (KWIC) sequence and a cartesian FLASH sequence, in terms of intrasubject differences in estimates of renal functional parameters and image quality characteristics. SUBJECTS AND METHODS. Ten healthy volunteers underwent repeated breath-hold KWIC and FLASH sequence examinations with temporal resolutions of 2.5 and 2.8 seconds, respectively. A two-compartment model was used to estimate MRI-derived perfusion parameters and glomerular filtration rate (GFR). The latter was compared with the iohexol GFR and the estimated GFR. Image quality was assessed using a visual grading characteristic analysis of relevant image quality criteria and signal-to-noise ratio calculations. RESULTS. Perfusion estimates from FLASH were closer to literature reference values than were the KWIC sequences. In relation to the iohexol GFR (mean [± SD], 103 ± 11 mL/min/1.73 m2), KWIC produced significant underestimations and larger bias in GFR values (mean, 70 ± 30 mL/min/1.73 m2; bias = −33.2 mL/min/1.73 m2) compared with the FLASH GFR (110 ± 29 mL/min/1.73 m2; bias = 6.4 mL/min/1.73 m2). KWIC was statistically significantly (p < 0.005) more impaired by artifacts than was FLASH (AUC = 0.18). The average signal-enhancement ratio (delta ratio) in the cortex was significantly lower for KWIC (delta ratio = 0.99) than for FLASH (delta ratio = 1.40). Other visually graded image quality characteristics and signal-to-noise ratio measurements were not statistically significantly different. CONCLUSION. Using the same postprocessing scheme and pharmacokinetic model, FLASH produced more accurate perfusion and filtration parameters than did KWIC compared with clinical reference methods. Our data suggest an apparent relationship between image quality characteristics and the degree of stability in the numeric model-based renal function estimates.